INFLUENCE OF HYPOXIA ON THE AMINO ACID COMPOSITION OF FETAL AMNIOUS WHICH IS BORN WITH SIGNS OF HYPOXIA - Zamasiy, A. A. (Scientific Progress & Innovations, 2019)
The article presents the results of studies on the influence of hypoxia on the amino acid composition of fe-tal amnious that are born with signs of hypoxia. The total content of amino acids and their derivatives in the amniotic fluid of functionally active newborn calves was 275.37±7.52 nmol/0.1 ml. Depending on the severi-ty of the hypoxic lesion, this indicator for amniotic fluid calves born with signs of hypoxia was 1.68, 1.23 and 1.23 times lower than that of functional ovary calves (p<0.01). In the calves born in the state of asphyxia or in the amniotic fluid contained in the meconium available (the first experimental group), the pool of free amino acids in the aforementioned fluid was found to be 2.34 times lower (p<0.001) than that of functionally active calves. The sum of essential amino acids in the amniotic fluid of the calves of the first experimental group was lower than that of functionally active newborn calves in 2.38 times, and the replacement − in 2.34 times (p<0.01). The main amino acid involved in the initial stage of this cycle is ornithine. Its content in the amniotic fluid of functionally active newborn calves was 3.43 ± 0.04 nmol/0.1 ml, and in calves born with signs of hypoxia, this indicator was 10.09, 3.30 (p<0.001 ) and 1.26 times lower (p<0.05). Citrulline in the amniotic fluid of calves in the control group was found at 3.91±0.25 nmol/0.1 ml. In the amniotic fluid, the calves of all three groups that were born with signs of hypoxia contained proline and oxyproline had the op-posite expression: (ie, the content of proline was lower, and the oxyproline was greater). Of considerable interest is the content of arginine, since it is the main source of NO in the body. The amount of glutamic acid and its amide (glutamine) in the amniotic fluid of functionally active calves was 9.36 % of all free amino ac-ids. In hypoxic calves, the amount of this acid and its amide was 2.18 times smaller than that of functionally active calves. The high content of ammonia in the amniotic fluid of hypoxic calves indicates a violation of the ammonia binding function of glutamine and its detoxification.